Theoretical foundations of estimated construction costs - Purs, G. A.; Samal, N. K. (Ways to Improve Construction Efficiency, 2019)
Determining the amount of financing at the stage of substantiating investments requires the use of a new methodology for an integrated assessment of the cost of construction, which will determine the required amount of funds at the stage of elaboration of a preliminary solution, evaluate the cost of multidisciplinary objects, select architectural and planning solutions taking into account customer requirements and financing conditions. The article is devoted to the study of the economic nature of the estimated cost of construction, as a result of which it has been shown that the definition of estimated cost, legally enshrined in the pricing of Belarus, requires refinement, since in addition to indicating that the estimated cost is calculated at various levels of consolidation, from the type of work to the entire facility, it is necessary to indicate the sources of information for its formation and emphasize the probabilistic nature, since the cost of construction is specified as the project details when passing waiting for the pre-investment and investment stages of the project. The existing methodology for determining the cost of construction at the pre-investment stage with the help of analogous facilities does not allow evaluating the investment project with the development of alternative functional planning solutions and calculating the estimated cost for each of the proposed project options. A study of a number of works by domestic and foreign scientists on the economic valuation of buildings made it possible to identify the shortcomings of the existing approaches to determining the estimated cost of construction, which are grouping data only by identifying complexes of homogeneous construction and installation works that are technologically related to each other, that is, it misses the possibility of highlighting individual estimates in the budget documentation premises, which would allow determining their reliable cost as separate building blocks for the optimal choice x architectural and planning decisions, as well as for the assessment of separate real estate objects, i.e. it is necessary to develop new approaches to calculating the estimated cost of construction to justify investments.